Анализ Фурье-спектра высокого разрешения полосы v6 молекулы CIS-C2H2D2 - Конов И. А. Иван Александрович; Чертавских Ю. В. Юлия Владимировна; Фомченко А. Л. Анна Леонидовна; Аслаповская Ю. С. Юлия Сергеевна; Жданович С. А. Станислав Андреевич; Зидо К. Кристиан (2015, 2015)
Заглавие с экрана